PENGARUH MODEL PEMBELAJARAN INQUIRY DAN GAYA KOGNITIF SISWA TERHADAP HASIL BELAJAR MATEMATIKA SISWA DI KELAS VIII SMP NEGERI 6 KERINCI - Trisna Rukhmana (Ensiklopedia of Journal, 2019)
This research aims to know the effect of Inquiry learning mode toward students’ mathematic achievement, the effect of students’ cognitive style toward students’ mathematic achievement the interaction effect between learning mode and students’ cognitive style toward students’ mathematic achievement at student grade VIII (Eight) SMP Negeri 6 Kerinci discrit academic year 2015/2016. The resarch conducted by using quasy experimental design research method follows nonequivalent control group design version by implementing factorial design 2 × 2. The population of the research are students of SMP Negeri 6 Kerinci discrit grade VIII odd term academic year 2015/2016. The study sample consisted of two class of experimental and one control class. Data is collected using two kinds of instruments namely instruments Group Embedded Figures Test (GEFT) to measure students' cognitive styles and mathematics achievement test students in essay form. Statistical test used is using ANOVA two paths to see the effect of the learning model and the effect of cognitive style on achievement as well as the interaction between the mathematical model of learning and cognitive styles of students towards mathematics student achievement. Further trials using t-test to see differences in student achievement based on students' cognitive styles. Result data analysis and statistical testing show that inquiry learning mode take effect toward Mathematic achievement, students’ cognitive style take effect toward Mathematic achievement, There is no interaction between learning mode and students’ cognitive style toward students’ Mathematic. Based on the results of this study it is suggested to the teachers, particularly the mathematics teacher that the implementation of the inquiry learning model can be developed as an innovation in teaching and learning process.